Synthesis and Anti-Plant Pathogenic Fungal Activity of Flavokawain-Derived Flavones and Related Flavones Against Rhizoctonia solani - Panuwat Onnom; Warot Chotpatiwetchkul; Jatuporn Meesin; Pilunthana Thapanapongworakul; Chokchai Kittiwongwattana; Nawasit Chotsaeng (Current Applied Science and Technology, 2023)
Flavones are organic compounds in the flavonoid family that have a diverse range of biological functions. In this research, many flavones with various substituents were designed and synthesized from flavokawains A, B, and C, and their chalcone derivatives via an iodine-catalyzed oxidative cyclization process. All synthetic flavones were investigated for antifungal activities against Rhizoctonia solani, a plant pathogenic fungus. At 400 µg, most of the substances did not inhibit the tested species and R. solani growth was inhibited by only o-bromoflavone (40) by 74.88±0.91%. This indicated that the detrimental effect of flavones depends on the type and position of substituent, with the ortho bromo group showing the most promise. The molecular docking study on the succinate dehydrogenase (SDH) enzyme revealed that the bromophenyl moiety (ring B) is a key molecular substructure of the flavone fungicide. The findings of this study will be used to develop novel plant pathogenic fungicides.
Keywords: Plant Disease Resistance and Genetics; Plant Pathogens and Fungal Diseases; Plant-Microbe Interactions and Immunity